Calidad de vida y síntomas depresivos de niños, niñas y adolescentes con enfermedades crónicas - Robles Méndez, Ismery Yaneth (Universidad Antonio Nariño, 2023)
Chronic diseases are those pathological processes of continuous and prolonged evolution, which rarely achieve a complete resolution or cure (1). These diseases can cause a high negative impact on a physical, emotional and social, both in the children and adolescents who suffer from them, as well as in their families. One of the possible consequences due to the emotional and psychosocial affectation, both of the patient and his family, caused by the presence of chronic diseases in general, is the alteration of his state of mental health and, together with this, one of the disorders with the highest prevalence such as depressive symptoms